2017
DOI: 10.1002/dvg.23023
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an inducible mouse model to reversibly silence Stat3

Abstract: Signal transducer and activator of transcription 3 (Stat3) is a transcription factor that has many essential roles during inflammation, development and cancer. Stat3 is therefore an attractive therapeutic target in many diseases. While current Stat3 knockout mouse models led to a better understanding of the role of Stat3, the irreversible nature of Stat3 ablation does not model the effects of transient Stat3 therapeutic inhibition, and does not inform on potential dosage effects of Stat3. Using RNAi technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…In this model, gastric adenomas spontaneously and reproducibly develop with 100% penetrance in 4-week-old mice with an absolute genetic dependence on bi-allelic expression of the il11ra and Stat3 genes, but completely independent of IL6 signaling (Jenkins et al, 2005;Ernst et al, 2008). Importantly, we had previously shown that therapeutic treatment of tumor-bearing, 10-to 13-weekold gp130 Y757F mice with either the antagonistic IL11-Mutein peptide (Putoczki et al, 2013), JAK1/2 kinase inhibitors , STAT3 antisense oligonucleotides (Ernst et al, 2008), or inducible short hairpin STAT3-RNA (Alorro et al, 2017), reduces tumor burden associated with reduced cell proliferation and increased apoptosis. Thus, we treated 13-week-old gp130 Y757F mice with A Crystal structure of the extracellular domains of the IL6 hexameric signaling complex (PDB ID: 1P9M; Boulanger et al, 2003), depicted in cartoon format.…”
Section: Bazedoxifene Blocks Il11 Signalingmentioning
confidence: 99%
“…In this model, gastric adenomas spontaneously and reproducibly develop with 100% penetrance in 4-week-old mice with an absolute genetic dependence on bi-allelic expression of the il11ra and Stat3 genes, but completely independent of IL6 signaling (Jenkins et al, 2005;Ernst et al, 2008). Importantly, we had previously shown that therapeutic treatment of tumor-bearing, 10-to 13-weekold gp130 Y757F mice with either the antagonistic IL11-Mutein peptide (Putoczki et al, 2013), JAK1/2 kinase inhibitors , STAT3 antisense oligonucleotides (Ernst et al, 2008), or inducible short hairpin STAT3-RNA (Alorro et al, 2017), reduces tumor burden associated with reduced cell proliferation and increased apoptosis. Thus, we treated 13-week-old gp130 Y757F mice with A Crystal structure of the extracellular domains of the IL6 hexameric signaling complex (PDB ID: 1P9M; Boulanger et al, 2003), depicted in cartoon format.…”
Section: Bazedoxifene Blocks Il11 Signalingmentioning
confidence: 99%
“…The second CAGs-rtTA;shStat3 mouse model, referred to as shStat3 hereafter, was generated to carry a GFP-linked, doxycycline (dox)-inducible Stat3 short hairpin RNA for the reversible silencing of Stat3 and has been characterised previously [ 19 ]. Two different controls were used to complement the dox-treated shStat3 cohort.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we also employed dox-treated CAGs-rtTA;shLuc (referred to as shLuc) transgenic mice, which harbour a GFP-linked irrelevant hairpin to account for any non-specific effects from the short hairpin RNA. Dox treatment resulted in Stat3 knockdown by 80% in multiple organs and cell types including the gastrointestinal tract, while Stat1 expression remained unaltered [ 19 ]. Immunohistochemistry confirmed a reduction in the expression of pSTAT3 in shStat3 mice after doxycycline treatment, but not in shStat3 chow and dox-treated shLuc controls ( Supplementary Figure S1D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations